1976
DOI: 10.1093/infdis/133.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Neuroadapted Mumps Virus in Brains of Newborn Hamsters after Intraperitoneal Inoculation

Abstract: Neuroadapted mumps virus produces systemic infection in newborn hamsters after intraperitoneal inoculation. Virus is disseminated via a low-level viremia and appears to enter the central nervous system by passage through the choroid plexus. At such sites, choroidal and ependymal epithelial cells are productively infected and become a source for further viral spread throughout the brain parenchyma. The development of neutralizing and hemagglutination-inhibiting antibodies in serum correlates with the clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Cells were infected/transfected, fixed, processed, and mounted as previously described (16). A primary anti-MuV F monoclonal antibody (5.418) was used at a dilution of 1:500 (30 50 ) of the viruses in the right parietal area of the skull, approximately 1 mm right of the midline and midway between the eye and the ear under mild isoflurane anesthesia (10 l). Fourteen to 50 animals per virus were infected.…”
Section: Viruses and Cells The Muvmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were infected/transfected, fixed, processed, and mounted as previously described (16). A primary anti-MuV F monoclonal antibody (5.418) was used at a dilution of 1:500 (30 50 ) of the viruses in the right parietal area of the skull, approximately 1 mm right of the midline and midway between the eye and the ear under mild isoflurane anesthesia (10 l). Fourteen to 50 animals per virus were infected.…”
Section: Viruses and Cells The Muvmentioning
confidence: 99%
“…Encephalitis in the brains of newborn hamsters infected with rodent brainadapted strains of MuV has been studied extensively (21). Both intracerebral inoculation and intraperitoneal inoculation with the MuV KH strain lead to widespread CNS infection and mortality (21,50). However, the hamster model is unable to discriminate between MuV strains with known differences in human neurovirulence; comparison of the neurovirulence of three strains of MuV revealed that the nonneurovirulent Jeryl Lynn vaccine was most similar to the rodent brain-adapted MuV KH strain (51).…”
mentioning
confidence: 99%
“…Mumps virus can also infect urinary tract, genital organs, pancreas, kidney and central nervous system (CNS). It is not yet wellknown how mumps virus spreads to the CNS, however, studies in newborn hamster model suggest that virus spreads by passage of infected mononuclear cells across the epithelium to epithelial cells of the choroid plexus (Fleischer & Kreth, 1982;Wolinsky et al, 1976). Alternatively, direct spread of virus is possible.…”
Section: Viral Pathogenesis and Invasion Central Nervous Systemmentioning
confidence: 99%
“…1K). Circulating leukocytes in viral dissemination have been reported in mumps and measles virus infections (13,19).…”
Section: Histopathology and Virus Detection In Tissuesmentioning
confidence: 99%